Robust generation of oligodendrocyte progenitors from human neural stem cells and engraftment in experimental demyelination models in mice. - Margherita Neri; Claudio Maderna; Daniela Ferrari; Chiara Cavazzin; Angelo L Vescovi; Angela Gritti (PLoS ONE)
Background Cell-based therapy holds great promises for demyelinating diseases. Human-derived fetal and adult oligodendrocyte progenitors (OPC) gave encouraging results in experimental models of dysmyelination but their limited proliferation in vitro and their potential immunogenicity might restrict their use in clinical applications. Virtually unlimited numbers of oligodendroglial cells could be generated from long-term self-renewing human (h)-derived neural stem cells (hNSC). However, robust oligodendrocyte production from hNSC has not been reported so far, indicating the need for improved understanding of the molecular and environmental signals controlling hNSC progression through the oligodendroglial lineage. The aim of this work was to obtain enriched and renewable cultures of hNSC-derived oligodendroglial cells by means of epigenetic manipulation. Methodology/principal findings We report here the generation of large numbers of hNSC-derived oligodendroglial cells by concurrent/sequential in vitro exposure to combinations of growth factors (FGF2, PDGF-AA), neurotrophins (NT3) and hormones (T3). In particular, the combination FGF2+NT3+PDGF-AA resulted in the maintenance and enrichment of an oligodendroglial cell population displaying immature phenotype (i.e., proliferation capacity and expression of PDGFRalpha, Olig1 and Sox10), limited self-renewal and increased migratory activity in vitro. These cells generate large numbers of oligodendroglial progeny at the early stages of maturation, both in vitro and after transplantation in models of CNS demyelination. Conclusions/significance We describe a reliable method to generate large numbers of oligodendrocytes from a renewable source of somatic, non-immortalized NSC from the human foetal brain. We also provide insights on the mechanisms underlying the pro-oligodendrogenic effect of the treatments in vitro and discuss potential issues responsible for the limited myelinating capacity shown by hNSC-derived oligodendrocytes in vivo.